Suppression of SBS in a photonic crystal fiber with periodically-varied core diameter - Stiller, Birgit; Lee, Min Won; Delqué, Michaël; Bouwmans, Géraud; Kudlinski, Alexandre; Beugnot, Jean Charles; Maillotte, Hervé; Sylvestre, Thibaut (Optics InfoBase Conference Papers, 2011)
We experimentally demonstrate 7 dB improvement in Brillouin suppression in a photonic crystal fiber by periodically varying the size of the air-hole-structure by only 7% amplitude while keeping a low attenuation coefficient. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29